Medical Student Perspectives on Undergraduate Oncology Education in the UK. Issue 8 (August 2022) - Heritage, S.R.; Lynch-Kelly, K.; Kalvala, J.; Tulloch, R.; Devasar, A.; Harewood, J.; Khoury, E.; Abdelwahed, A.; Fung, A.; Bigogno, C.M.; Gray, R.; Keshwara, S.; et al.
Abstract: Aims: The British Oncology Network for Undergraduate Societies (BONUS) surveyed students who attended an oncology revision day to determine their views on the current quantity, quality and type of curriculum-based oncology teaching they have experienced. Materials and methods: Students attending two BONUS revision days received a questionnaire assessing their experience of oncology teaching within the medical curriculum and interest in pursuing a future career in oncology using a 10-point Likert scale. Data were collected with informed consent to be anonymised and used for research. Student demographics and qualitative and quantitative data about experiences of oncology education were analysed. Results: In total, 451 students registered to attend the revision days. After removal of duplicates, non-responders and non-UK participants, responses from 153 students studying across years 1–6 at 22 UK medical schools were analysed. The mean quantity of oncology lectures students reported receiving was 8.9 hours and the mean quantity of clinic/ward-based oncology teaching was 7.5 hours. Ninety (62.1%) of the 145 students who responded to the relevant question reported that they had received dedicated teaching in oncology. Students who had received dedicated oncology teaching reported a statistically significantly higher mean quality 6.1 (95% confidence interval 5.6–6.5) versus 5.0 (95% confidence interval 4.3–5.5; P = 0.003) and quantity 5.2 (95% confidence interval 4.7–5.6) versus 4.3 (95% confidence interval 3.7–4.9; P = 0.03) of oncology teaching compared with those who had not received this. Conclusion: Appropriate oncology education is essential for all medical students due to the high prevalence of cancer. All future doctors need the appropriate knowledge and communication skills to care for cancer patients. Our analysis provides quantitative evidence to support the value of specialist oncology teaching within the medical school curriculum in improving student-reported experience. National student-led revision days and events may widen interest in a future career in oncology and aid collaboration between oncology societies. It is important for the general undergraduate medical curriculum to integrate specialty content. An integrated curriculum should facilitate a holistic approach that spans prevention, screening, treatment and palliation rather than being split by subspeciality. Highlights: Student-led national events may widen interest in oncology and aid collaboration between medical schools. Mentorship schemes and online education resources may increase exposure and interest in oncology. The undergraduate medical curriculum should focus on holistic oncology training.